The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10286-016-0383-5
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for refractory adrenergic crisis in familial dysautonomia

Abstract: Objective Adrenergic crises are a cardinal feature of familial dysautonomia (FD). Traditionally, adrenergic crisis have been treated with the sympatholytic agent clonidine or with benzodiazepines, which can cause excessive sedation and respiratory depression. Dexmedetomidine is an α2A-adrenergic agonist with greater selectivity and shorter half-life than clonidine. We aimed to evaluate the preliminary effectiveness and safety of intravenous dexmedetomidine in the treatment of refractory adrenergic crisis in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…46 Acute episodes usually respond to intravenous dexmedetomidine, which has the advantage of rapid onset combined with a short half-life, allowing it to be tightly titrated. 47 Another approach to centrally inhibit sympathetic outflow is the α-2 adrenergic agonist, clonidine. 1 While effective, clonidine often causes extreme fatigue and/or rebound hypertension, making it a poor choice for patients in the long term.…”
Section: Principles Of Managementmentioning
confidence: 99%
“…46 Acute episodes usually respond to intravenous dexmedetomidine, which has the advantage of rapid onset combined with a short half-life, allowing it to be tightly titrated. 47 Another approach to centrally inhibit sympathetic outflow is the α-2 adrenergic agonist, clonidine. 1 While effective, clonidine often causes extreme fatigue and/or rebound hypertension, making it a poor choice for patients in the long term.…”
Section: Principles Of Managementmentioning
confidence: 99%
“…20 Additionally, two studies report the successful cessation of autonomic dysfunction with an associated decrease in blood pressure, heart rate, and improved symptom control utilizing dexmedetomidine as an infusion. 21,22 Furthermore, in a metaanalysis of adult critical care patients evaluating the overall efficacy and safety of dexmedetomidine showed dexmedetomidine was associated with a 48-hour reduction in ICU length of stay, mechanical ventilation duration, and delirium occurrence compared with lorazepam, midazolam, and propofol. Dexmedetomidine was also associated with an increase in bradycardia and hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, plasma norepinephrine levels on day 8 were 20% lower in the group who received propranolol and clonidine compared with placebo. 22 Diverse treatment options have been reported for aborting or decreasing the episodic frequency of PSH in pediatric patients with varying success. In our patient, traditional methods utilizing opiates and sedatives were not successful in mitigating episodes of PSH.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously reported that the intravenous formulation of dexmedetomidine was safe and effective to treat adrenergic crises in these patients without causing respiratory depression [2]. …”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported the successful use of intravenous dexmedetomidine, a centrally acting α 2 adrenergic agonist, to abort severe adrenergic crisis in patients with FD [2]. Dexmedetomidine has the advantage of having a rapid onset and very short half-life, but requires intravenous administration in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%